Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Ratcliffe, Sophia; Wirth, Christian; Jucker, Tommaso; der Plas, Fons; Scherer‐Lorenzen, Michael; Verheyen, Kris; Allan, Eric; Benavides, Raquel; Bruelheide, Helge; Ohse, Bettina; Paquette, Alain; Ampoorter, Evy; et al. (Ecology letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.